2008
DOI: 10.1029/2007gl030331
|View full text |Cite
|
Sign up to set email alerts
|

A combined organic‐inorganic sea‐spray source function

Abstract: [1] This study presents a novel approach to develop a combined organic-inorganic sub-micron sea-spray source function for inclusion in large-scale models. It requires wind speed and surface ocean chlorophyll-a concentration as input parameters. The combined organic-inorganic source function is implemented in the REMOTE regional climate model and sea-spray fields are predicted with particular focus on the North East Atlantic. The model predictions using the new source functions compare well with observations of… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

8
222
1
2

Year Published

2008
2008
2018
2018

Publication Types

Select...
9

Relationship

0
9

Authors

Journals

citations
Cited by 208 publications
(233 citation statements)
references
References 19 publications
(27 reference statements)
8
222
1
2
Order By: Relevance
“…During winter the highest concentrations are determined over Eastern Europe due to domestic heating. Even higher POC concentrations are found during summer in the marine boundary layer where POC is released together with sea salt -both in the accumulation mode -dependent on wind speed (O'Dowd et al, 2008). This source of POC has not been taken into account before.…”
Section: Carbonaceous Aerosolsmentioning
confidence: 95%
See 1 more Smart Citation
“…During winter the highest concentrations are determined over Eastern Europe due to domestic heating. Even higher POC concentrations are found during summer in the marine boundary layer where POC is released together with sea salt -both in the accumulation mode -dependent on wind speed (O'Dowd et al, 2008). This source of POC has not been taken into account before.…”
Section: Carbonaceous Aerosolsmentioning
confidence: 95%
“…-Considerable OC concentrations are determined in the marine boundary layer during summer when POC is released together with sea salt -both in the accumulation mode -dependent on wind speed (O'Dowd et al, 2008). This source of POC has not been taken into account before.…”
Section: Discussionmentioning
confidence: 99%
“…Recent studies suggest that a fraction of submicron sea spray may be organic, rather than pure salt. Although mixed organic/salt flux parameterisations have been constructed from observations in one ocean [O'Dowd et al, 2008], it is not known to what extent the dependence of flux on wind speed will depend on the variable organic content, nor how the organic fraction varies in different oceans. We therefore restrict our study to the Mårtensson scheme for pure salt, which has been shown to agree well with size distribution measurements south of 45°S [ Pierce and Adams, 2006].…”
Section: Methodsmentioning
confidence: 99%
“…Marine aerosol consists of sea salt, primary organics from surface films and secondary sulfate aerosols produced from DMS released by phytoplankton [52,53]. Emission fluxes of primary marine aerosol species depend predominantly on surface wind speeds.…”
Section: Marine Aerosolmentioning
confidence: 99%